Regulasi Penggunaan Uang Digital Dagcoin dalam Prespektif Hukum Islam dan Hukum Positif - Hasan, Maisyarah Rahmi (el Buhuth: Borneo Journal of Islamic Studies, 2018)
Dagcoin digital currency is one of the tools of online-based transaction payments that increasingly growing in the global economy. Nowadays The Investors interest to invest digital currency. Indonesia is a law country must establish certain laws related to digital currency that began to spread and used as a means of exchange or means of payment in Indonesia. This study is a normative juridical study that examines the rules relating to the use of money in the sale and purchase transactions and investment in the perspectives of Islamic law and Positive Law in Indonesia. The results of this study found that in Islam the use of digital currency in the purchase transactions and investment is not in accordance with the Shari'ah because it does not fulfill the enquires that exist in transactions using digital currency such as dagcoin. The existence of elements of gharar and maisir is the main reason for this digital money is not legitimate in Islam. As mentioned at Fatwa DSN-MUI Number 28 / DSN-MUI / III / 2002 on the exchange of money. Whereas in view of the positive Law has been described in Act No. 7 of 2011 on money, then digital money cannot be said as money because the conditions set in the law are not in digital money, then Bank Indonesia Regulation Number 18/40 / PBI / 2016 on the payment of electronic transactions is also not met in transactions that exist on the use of digital money dagcoin. So does the electronic transaction information law (ITE). Unclear regulation of the use of digital currency makes some users feel restless.